2017
DOI: 10.2174/1573397113666170704102444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Pulmonary Manifestations of Systemic Lupus Erythematosus

Abstract: There are no specific guidelines for the management of these manifestations and therapeutic approach remains empiric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 0 publications
0
94
0
10
Order By: Relevance
“…A retrospective study demonstrated that DAH constituted 3.7% of systemic lupus erythematosus (SLE) admissions within a single institution [4]. As such, evaluation of DAH should include diagnostic testing not only for secondary APS but also primary APS as this may be a less common initial manifestation of these disease processes [[1], [2], [3],[5], [6], [7], [8], [9]]. Primary and secondary APS differ in that secondary APS has a concomitant diagnosis of another disease process, often SLE [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study demonstrated that DAH constituted 3.7% of systemic lupus erythematosus (SLE) admissions within a single institution [4]. As such, evaluation of DAH should include diagnostic testing not only for secondary APS but also primary APS as this may be a less common initial manifestation of these disease processes [[1], [2], [3],[5], [6], [7], [8], [9]]. Primary and secondary APS differ in that secondary APS has a concomitant diagnosis of another disease process, often SLE [8].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the variation in etiologies of APS associated DAH, whether primary or secondary, treatment should begin with corticosteroids [2]. However, because there is no confirmed treatment regimen among DAH patients with either form of APS, management can be difficult [7]. There is data to suggest that different immunohistochemical characteristics of those presenting with either form of APS may have different incidences of pathology leading to pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Auch wenn die Nieren-und ZNS-Beteiligung als die prognostisch schwerwiegends-ten Organbeteiligungen des systemischen Lupus erythematodes (SLE) gelten, sind bei diesem Krankheitsbild kardiale Manifestationen am vielfältigsten und eindeutig am häufigsten (9,15). Im Rahmen einer krankheitstypischen (aseptischen) Serositis, häufig begleitet von Temperaturen, Hautveränderungen und Gelenksymptomen, finden sich Perikarditiden im kumulativen Krankheitsverlauf in fast der Hälfte der Fälle und die OR hierfür beträgt über 30 (16).…”
Section: Systemischer Lupus Erythematodesunclassified
“…Herzklappenveränderungen (meist Verdickungen der Aorten und Mitralklappe) sind beim Lupus ebenfalls häufig (OR 11, ca. 50 % der Fälle) zu finden (15), wobei eine hohe Assoziation zum 1986 definierten Antiphospholipidsyndrom (APS) besteht. Dieses tritt bei ca.…”
Section: Systemischer Lupus Erythematodesunclassified
See 1 more Smart Citation